Pengaruh Supervisi Pengawas dan Kompetensi Guru Terhadap Kualitas Pembelajaran SMP di Kecamatan Liukang Tangaya Kabupaten Pangkep - Irwandi, Nasvar; Yunus, Muh; Syarifuddin, Syarifuddin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
The objective of this research is to analyze the influence of supervisor supervision and teacher competence on the quality of learning at Junior High Schools (SMP) throughout Liukang Tangaya District, Pangkep Regency. Specifically, this study aims to reveal the extent of the partial influence of supervisor supervision, the partial influence of teacher competence, and the simultaneous influence of both variables on learning quality in a remote archipelago region. The focus of this research is to address educational challenges in areas characterized by geographical accessibility constraints and limited resources. The research methodology employed is a quantitative research design with a survey approach. The research population consists of all junior high school teachers in Liukang Tangaya District, totaling 140 individuals, with a research sample of 42 teachers selected using purposive sampling techniques. Data collection was conducted through questionnaires using a Likert scale, in-depth interviews with principals and teachers, and documentation studies. Data analysis involved descriptive and inferential statistics, including classical assumption tests and multiple linear regression analysis performed with SPSS software. The results of the study indicate that both supervisor supervision and teacher competence have a positive and significant influence on the quality of learning. Partially, the supervisor supervision variable contributes significantly (tcount 5.080 t table 2.021), while the teacher competence variable exerts a more dominant influence (t count 6.870 t table 2.021). Simultaneously, these two variables have a very strong influence of 96.4% on the quality of learning (R2 = 0.964), while the remaining 3.6% is influenced by other factors outside this study. These findings confirm that the synergy between professional guidance by supervisors and the strengthening of educator competence is the primary key to maintaining educational quality in disadvantaged areas.